Eating problems among old home care clients - Annina Salmi; Kaija Komulainen; Annamari Nihtilä; Miia Tiihonen; Irma Nykänen; Sirpa Hartikainen; Anna L. Suominen (Wiley, 2022)
Abstract Aims The purpose was to examine the prevalence and determinants of self‐reported eating problems in old home care clients, screened separately by a clinical nutritionist and a dental hygienist. Methods and Results The data came from the Nutrition, Oral Health and Medication (NutOrMed) study, the participants of which were ≥75‐year‐old home care clients living in Finland. The structured interviews were conducted at the participants' (n = 250) homes. Of the participants, 29% reported poor appetite, 20% had problems with chewing, and 14% had problems with swallowing when asked by a clinical nutritionist. Additionally, 18% reported oral health‐related eating problems when asked by a dental hygienist. Participants with continuous xerostomia (odds ratio [OR]: 3.0, 95% confidence interval [CI]: 1.0-9.0) or poor self‐reported oral health (OR: 4.3, 95% CI: 1.4-13.0) had a higher risk for problems with chewing when asked by a clinical nutritionist. Edentulous participants (OR: 3.5, 95% CI: 1.2-10.9) and participants with toothache or problems with dentures (OR: 10.3, 95% CI: 4.0-26.0) had a higher risk for oral health‐related eating problems when asked by a dental hygienist. Conclusion Eating problems are common in older adults, and interprofessional collaboration is required for their identification and alleviation.